Morphological and spectrometric studies of blood plasma from the patients with cerebral aneurysms - Buloichik, Janne I.; Zajogin, Anatoli P.; Nechipurenko, Nataliya I.; Patapovich, Marya P.; Pashkovskaya, Irina D. (Journal of the Belarusian State University. Physics, 2018)
An integral estimation of the content of essential elements in blood plasma of the patients with cerebral aneurysms is presented. Significant deviations from the normal concentration of the elements under study has been revealed for the majority of the patients both before and after surgery. The obtained results are supported by the morphology of the dried blood-plasma drops and by the quantitative data acquired with the use of laser atomic emission spectrometry for the spatial distribution of calcium on the surface and within the layers of these drops. The exhibited features in the clinical course of the disease point to the necessity to broaden the list of remedies used during medicamentous therapy to correct metabolism of the minerals. The experimental data may form the basis for further improvement of the methods intended to correct insufficient levels of the functional resources of a human organism and for working-out the adequate system of rehabilitation measures.
Keywords: atomic-emission spectral analysis; blood plasma; biological fluids; drop morphology; laser atomic-emission spectrometry; spatial distribution of calcium; layer-by-layer analysis